Hydrothermal Carbonization - Reza, M. Toufiq (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on recent progress on hydrothermal carbonization (HTC) to upcycle wet waste biomass like sewage sludge and corn stover into valuable energy and materials like carbon quantum dots (CQDs). The reprint also reports fundamentals of HTC and compares with vapothermal carbonization.